Genetic Polymorphism of NQO1 Influences Susceptibility to Coronary Heart Disease in a Chinese Population: A Cross-Sectional Study and Meta-Anaylsis - Zhou YY; Sun JH; Wang L; Cheng YY (Dove Medical Press, 2023)
Ying-Yan Zhou,1,* Jing-Hua Sun,2,* Li Wang,1 Yan-Yan Cheng1 1Department of Cardiovascular Medicine, Haikou Third People's Hospital, Haikou, 571700, People's Republic of China; 2Department of Laboratory Medicine, First Medical Centre of Chinese PLA General Hospital, Beijing, 100853, People's Republic of China*These authors contributed equally to this workCorrespondence: Yan-Yan Cheng, Department of Cardiovascular Medicine, Haikou Third People's Hospital, Haikou, 571700, People's Republic of China, Email cyy570775779@163.comObjective: The present study is to explore the association between NQO1 gene polymorphism and coronary heart disease (CHD) risk.Methods: This research were selected 80 CHD patients as the observation group and 130 healthy people who participated in normal physical examination during the same period as the control group. NQO1 gene polymorphism was detected by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. In addition, we conducted a meta-analysis to summarize the results of three relevant previously published adult population studies on the association between NQO1 gene polymorphism and coronary heart disease (CHD) risk.Results: There were three genotypes (CC, CT, and TT) for NQO1 C609T polymorphism. The significant associations were found in TT genotype and T allele (all p< 0.05). Specifically, People with the TT genotype have 2.06 times CHD risk as those with the CC genotype. And People with the T allele have 1.62 times CHD risk as those with the C allele. No significant association was found by any genetic models in the meta-analysis (all p > 0.05).Conclusion: NQO1 gene polymorphism increased the CHD risk in a Chinese population. Combined with individual gene polymorphism, the accuracy of risk assessment for CHD can be improved and individualized health education can be provided for CHD patients by nurses.Keywords: NQO1, gene polymorphism, coronary heart disease, meta-analysis, nursing